Hypoxia inducible factor-1α mediates the profibrotic effect of albumin in renal tubular cells. Issue 1 (December 2017) - Hu, Junping; Wang, Weili; Zhang, Fan; Li, Pin-Lan; Boini, Krishna; Yi, Fan; Li, Ningjun
Abstract Proteinuria is closely associated with the progression of chronic kidney diseases (CKD) by producing renal tubulointerstitial fibrosis. Over-activation of hypoxia inducible factor (HIF)-1α has been implicated in the progression of CKD. The present study tested the hypothesis that HIF-1α mediates albumin-induced profibrotic effect in cultured renal proximal tubular cells. Incubation of the cells with albumin (40 μg/ml) for 72 hrs significantly increased the protein levels of HIF-1α, tissue inhibitor of metalloproteinase (TIMP)-1 and collagen-I, which were blocked by HIF-1α shRNA. Albumin also stimulated an epithelial-mesenchymal transition (EMT) as indicated by the decrease in epithelial marker E-cadherin, and the increase in mesenchymal markers α-smooth muscle actin and fibroblast-specific protein 1. HIF-1α shRNA blocked albumin-induced changes in these EMT markers as well. Furthermore, albumin reduced the level of hydroxylated HIF-1α, indicating an inhibition of the activity of prolyl-hydroxylases, enzymes promoting the degradation of HIF-1α. An anti-oxidant ascorbate reversed albumin-induced inhibition of prolyl-hydroxylase activity. Overexpression of prolyl-hydroxylase 2 (PHD2) transgene, a predominant isoform of PHDs in renal tubules, to reduce HIF-1α level significantly attenuated albumin-induced increases in TIMP-1 and collagen-I levels. These results suggest that albumin-induced oxidative stress inhibits PHD activity to accumulate HIF-1α, which mediates albumin-induced profibrotic effects in renal tubular cells.